Physiological and biomechanical analyses of water polo goalkeepers - Nekooei, Pooya; Majlesi, Sara (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The aim of this study was to examine the physiological and biomechanical demands of water polo goalkeepers. One of the important positions in the water polo is the goalkeeper because the goalkeeper is the last defense of the team. The goalkeeper is the results of the one team if teams have a strong goal keeper then those teams are successful in their competition. Also the control of the game are in goalkeeper hand, the goal keeper must control the speed of the game because from the point of physiology , the goalkeeper have low heart rate and intensity in greater duration of the game than other field players. All the goalkeepers for being successful in their position, they have to exercise on their eggbeater kick. Because the egg better kick is the most important skill for goalkeepers. As the point of biomechanics the Eggbeater kick is strongly related to foot speed and ankle rotations. In addition the better performance of eggbeater kicks more focusing on Anteroposterior (backward and forward) motions and less vertical motions of the feet than poorer performance.